Ocular Affection as an Extraintestinal Manifestation in Cases of Inflammatory Bowel Disease at the Kafrelsheikh Governorate - Ahmed, Mohammed Hussien; Elashery, Mohammed; Maksoud, Hebatallah Abdel; Mahros, Aya Mohammed (Journal of Coloproctology, 2021)
Introduction The manifestations of inflammatory bowel disease (IBD) are not restricted to the gastrointestinal tract. Musculoskeletal conditions are considered the most common extraintestinal manifestations, followed by mucocutaneous and ocular diseases. Many general practitioners are unaware of the variety and severity of the ocular affection in IBD patients.Objective To assess the prevalence of extraintestinal manifestations in IBD patients at Kafrelsheikh governorate, and to evaluate the different ocular manifestations and their relationship to the severity of the disease.Methods A cross-sectional study evaluating 120 patients treated at the Kafrelsheikh University Hospital. The diagnosis of IBD was made between December 2018 and December 2019 through clinical, endoscopic and histopathological examinations. All patients were assessed for any extraintestinal manifestation or evidence of ocular affection through slit-lamp examinations, tonometry, visual acuity, and indirect ophthalmoscopy.Results The mean age of the sample was 35.5 ±  13.3 years. In total, 52 (43.3%) patients were male and 68 (56.7%) were female. Ocular manifestations represent ∼ 22.5% of extraintestinal manifestations. The most common ocular findings were conjunctivitis (25.8%) and anterior uveitis (10.8%), followed by scleritis (9.2%) and cataract (8.3%). Other extraintestinal manifestations were observed in 41 (34.1%) 29 (29.9%) of ulcerative colitis cases, and 12 (52%) of Crohn disease cases. There was no statistically significant difference in the presence of ocular involvement in relation to the two types of IBD included in the Montreal classification.Conclusion Ocular manifestations in cases of IBD are common and usually nonspecific in presentation. The severity of the IBD does not reflect the severity of the ocular affection.
Keywords: inflammatory bowel disease; ocular manifestations